Natural Moisturizer Based on Green Grass Jelly (Cyclea Barbata Miers) with Stevia Leaf Addition (Stevia Rebaudiana Bertoni) - Ahmad Thoriq Mubarok; Kun Harismah (Jurnal Dedikasi, 2020)
Skin moisturizer is a chemical that can protect the skin from the sun. Natural ingredients that can be used as a moisturizer are Green Grass Jelly. Green Grass Jelly leaves contain antioxidants that can prevent skin aging. The purpose of this study was to analyze the application of Green Grass Jelly and Stevia as a facial moisturizing ingredient. The variables used in this study were Green Grass Jelly consentration of 2.5%, 5%, 7.5%, and 10%. And stevia benefits 0%, 5%, 7.5%, 10% and 12.5%. the method used is Green Grass Jelly extraction, stevia extraction and moisturizing preparations. The test used were homogeneity analysis, pH measurement, specific gravity, dispersion, emulsion reliability, and organoleptic. Based on SNI-16-4399-1996 all samples that have been made meet the existing standards and also suitable sample formulations are F(D) ie 2.5% Green Grass Jelly composition and 5% stevia.